Solar-blind ultraviolet-C persistent luminescence phosphors - Xianli Wang (Nature Portfolio, 2020)
Ultraviolet-C radiation sources are important for disinfection and photochemical water purification, but development of persistent phosphors is needed for other applications. Here the authors report praseodymium-doped silicate ultraviolet-C persistent phosphors for self-sustained glowing tags in bright light.